Office Stationery Inventory Management System Using the Waterfall Method at PT Inalum - Ramadani, Putri; Pandia, Nur Aisyah; Sriani, Sriani (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Management of office stationery (ATK) is an important aspect in supporting daily operations at PT. Indonesia Asahan Aluminum. In this context, the ATK management system which is still carried out manually has resulted in various problems, such as recording errors, delays in preparing reports, and inaccuracies in budget submissions. This research aims to design and implement a web-based information system that can increase the efficiency and effectiveness of managing ATK usage in the SIT Section.The method used in this research is the waterfall system development method, which consists of several stages: needs analysis, system design, implementation, testing, and implementation. The results of the analysis show that the current manual process has a recording error rate of up to 15% of total transactions and the annual report preparation time takes up to two weeks. With this new information system, it is hoped that it can reduce recording errors to less than 5% and speed up the time for preparing reports to just three days.